Adapted Guidelines for Malaria Case Management in Sudan - Samah Elhassan; Sahar Khalid Mohamed; Khlood Fathi Hassan Alnaeem; Ahmed Abdulgadir Noureddin; Samah Kamaleldeen Bakrri Abass; Fadwa Mohamed Saad; Technical Advisory Committee (Sudan Journal of Medical Sciences)
Background: Malaria is a major public health hazard in Sudan. The latest update to the malaria diagnosis and treatment protocol in Sudan was in 2017, after which multiple developments in the global guidelines for malaria case management have taken place. Sudan’s Federal Ministry of Health (FMOH) has updated its malaria case management policy to guide healthcare workers in making informed decisions about malaria diagnosis, treatment, and prevention. Methods: The National Malaria Control Program (NMCP) selected a multidisciplinary Technical Advisory Committee (TAC) balanced to bring together diverse expertise. The committee convened with the NMCP writing team to propose, discuss, and approve updates to the malaria case management protocol. Protocol updates were prioritized based on the guidelines’ efficacy, safety, and cost-effectiveness. Results: The management guidelines for severe malaria were updated so that parenteral artesunate is the first-line treatment, with parenteral quinine reserved as second-line therapy. Other updates include the adoption of oral artemetherlumefantrine (AL) as the first-line treatment for uncomplicated malaria in the first trimester of pregnancy. The 2023 protocol upheld the 2017 treatment guidelines for uncomplicated malaria in other groups, including children, adults, and pregnant women in their second and third trimesters, with AL as the first-line treatment and dihydroartemisinin-piperaquine (DHAP) as the second-line treatment. Conclusion: Key changes in the 2023 protocol include updates to the treatment guidelines for severe malaria in all patient groups and uncomplicated malaria in the first trimester of pregnancy. Future adjustments to the malaria protocol will take place in accordance with changes in the local context of Sudan as well as global malaria guidelines.